2005
DOI: 10.1111/j.1752-7325.2005.tb02793.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Utilization of Dental Care Services Among Chinese- and Russian-Speaking Immigrant Elders

Abstract: Although Chinese- and Russian-speaking elders have similar immigrant experiences and share the same geographic location and urban setting, the two groups have different patterns of dental service use. These differences may be due to differences in socio-demographic characteristics, values, attitudes and knowledge of oral health and dental care, and unique cultural backgrounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 19 publications
(5 reference statements)
4
61
3
Order By: Relevance
“…However, the results are likely to be inconclusive given the caveat of the BRFSS sample excluding non-English speaking individuals in the study. The rates of dental cleaning for Asian Americans in our study were higher than the rate reported from Wu et al’s (7) study conducted among Chinese American elders aged 60 and older in 2000. One major reason for the rate discrepancy is likely due to the differences in data collection: the previous one was conducted in Chinese and the BRFSS survey was conducted in English.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…However, the results are likely to be inconclusive given the caveat of the BRFSS sample excluding non-English speaking individuals in the study. The rates of dental cleaning for Asian Americans in our study were higher than the rate reported from Wu et al’s (7) study conducted among Chinese American elders aged 60 and older in 2000. One major reason for the rate discrepancy is likely due to the differences in data collection: the previous one was conducted in Chinese and the BRFSS survey was conducted in English.…”
Section: Discussioncontrasting
confidence: 80%
“…Using the National Health Interview Survey (NHIS) (1997–2000) data, one descriptive study reported that 58% of the Asians aged 65 and above had visited a dentist in the previous year, slightly higher than the rate in Whites (56.6%); while the rate for Asians aged 45–64 was 66.1%, slightly lower than their white counterparts (67.6%) (6). While the NHIS study was administered in English to the Asian participants, using a convenient sample, another study conducted among Chinese American elders in their native language found that only 47% of the participants aged 60 and above reported having a dental visit within the previous year (7). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of dental services increased with length of residence in the United States among Chinese elderly immigrants [34] and adults of Hispanic or Asian origins [35], but not among the Russian elderly [34]. English proficiency was associated with dental visit in Hispanic adults but not in Asians [35].…”
Section: Resultsmentioning
confidence: 99%
“…A set of independent variables that were found in previous studies to be important predictors and that were available in the Susenas data was selected as a set of possible factors affecting the perceived need for and utilization of dental care services (6)(7)(8)(9). In the present study, the independent variables comprised of age (<15, 15-29, 30-44, 45-59, >60 years), gender (female or male), living standard quintiles (1st to 5th quintile), residence (rural or urban), macroregions (Sumatra, Java, Lesser Sunda Islands, Kalimantan, Sulawesi, and Maluku Islands including West Papua), and health insurance entitlement (uninsured or insured).…”
Section: Independent Variablesmentioning
confidence: 99%